Efficacy of Routine Fecal Microbiota Transplantation for Treatment of Recurrent Clostridium difficile Infection: A Retrospective Cohort Study. (1st July 2019) - Nowak, Alexandra; Hedenstierna, Magnus; Ursing, Johan; Lidman, Christer; Nowak, Piotr
Abstract : Background . Patients with recurrent Clostridium difficile infections (CDIs) constitute an increasing treatment problem. Fecal microbiota transplantation (FMT) has shown promising results of treating recurrent CDI, where treatment with antibiotics fails repeatedly. Our study describes retrospective cohort treated with FMT at two major hospitals in Stockholm. Methods . Medical records of all patients with recurrent CDI treated with FMT during the period 2013–2017 were reviewed. We evaluated cure of CDI-related diarrhea without relapse 10 weeks after FMT. Results . 47 patients were included. One treatment cured 25 patients (53%), and more than one treatment cured 32 patients (68%). Treatment outcome did not vary significantly with treatment with fresh donor feces or frozen fecal culture, days of use of antibiotics or days of hospitalization prior to CDI, and renal function or time from the first CDI to therapy. Treatment failure was associated with a significantly lower Karnofsky performance status score (70 points vs 90, p = 0.02 ). Conclusion . Fecal instillation, for the treatment of relapsing CDI, is a promising approach, with 68% success rate reported in this study. The success rate of FMT is high, regardless of multiple comorbidities, extended use of antibiotics, or long time hospitalization. Although generally FMT is performed with fresh donor feces, our data show that the usage of frozen fecal culture could be an effective treatment alternative in recurrent CDI.